Pengawetan Ekstrak Pewarna Alami dari Daun dan Kulit Buah Kakao (Theobroma cacao L.) - Agustin, Veni Tri; Rahayuningsih, Edia; Mindaryani, Aswati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Indonesia has abundant natural resources that are very potential and prospective as raw materials for natural dyes, one of which is the leaves and skins of cocoa pods (Theobroma cacao L.). The purpose of this study is to determine the concentration of preservatives that can effectively inhibit the biodegradation reaction of natural dyes in the extract of leaves and skins of cocoa pods. Extracts of natural dyes that have been centrifuged and preservatives was added, then stored in a closed reactor. The preservatives used are benzoic acid and chitosan. Extraction is carried out for 20 days. Every 2 days, extract was analyzed from the reactor to determine the colorant concentration using gravimetric method. Besides benzoic acid, the same experiments was also carried out on another chitosan dissolved in 2% acetic acid solution. The results showed that the addition of benzoic acid and chitosan dissolved in 2% acetic acid solution can inhibit the biodegradation of leaves and skins of cocoa pods extract. Preservative concentrations of 0.50% benzoic acid and 0.25% chitosan are effective preservatives to inhibit the biodegradation reaction